Аналіз впливу штучного інтелекту на захищеність інформаційних систем - Назаренко, Д. М. (ХНУРЕ, 2023)
In today's digital landscape, where cyber security threats are becoming increasingly complex and distinct, the use of Artificial Intelligence (AI) in cyber defense is becoming a key factor in determining information systems protection strategies. The application of AI in cyber security opens up new perspectives in detecting threats, adapting to evolving attacks, and increasing the effectiveness of cyber defense. The detailed impact of AI on the security of information systems is considered and innovative approaches that change the landscape of cyber security are highlighted.
Keywords: захищеність інформаційних систем; штучний інтелект